Endometriosis. Guideline of European Society of Human Reproduction and Embryology - 2022 - Reproduct Editor (Publishing House TRILIST, 2022)
The European Society of Human Reproduction and Embryology (ESHRE) developed the current clinical practice guideline, to provide clinical recommendations to improve the quality of healthcare delivery within the European field of human reproduction and embryology. This guideline represents the views of ESHRE, which were achieved after careful consideration of the scientific evidence available at the time of preparation. In the absence of scientific evidence on certain aspects, a consensus between the relevant ESHRE stakeholders has been obtained. This document is the second update of the ESHRE Guidelines on Endometriosis (2014). However, there still remain many unanswered questions for which no, or only poor quality or little data are available. The aim of clinical practice guidelines is to aid healthcare professionals in everyday clinical decisions about appropriate and effective care of their patients. The guideline covers the care provided by secondary and tertiary healthcare professionals who have direct contact with, and make decisions concerning, the care of women with endometriosis. Although primary healthcare providers are not the main target users of this guideline, it may be of interest for them too. This guideline offers best practice advice on the care of women with suspected and confirmed endometriosis. Recommendations are provided on diagnosis and treatment for both relief of painful symptoms and for infertility due to endometriosis. Specific recommendations are provided on management of patients in whom endometriosis is found incidentally (without pain or infertility), adolescents and menopausal women with endometriosis. Information on risk factors for endometriosis and associations with other diseases is provided, with recommendations on prevention and monitoring.